2021
DOI: 10.33085/jkg.v4i2.4794
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kejadian Stroke pada Pasien Hipertensi (Analisis Data Sekunder IFLS 5)

Abstract: Angka prevalensi stroke di Indonesia berdasarkan diagnosis pada penduduk umur ≥ 15 tahun pada tahun 2007-2018 menunjukkan adanya peningkatan, serta sebanyak 51% kematian karena stroke disebabkan oleh hipertensi. Hal tersebut menjadi alasan pentingnya dilakukan upaya pencegahan stroke pada penderita hipertensi. Tujuan penelitian adalah untuk menganalisis hubungan umur, jenis kelamin, klasifikasi tekanan darah, lama menderita hipertensi, kepatuhan minum obat antihipertensi, penyakit diabetes, penyakit jantung de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Managing blood pressure along with MAP can reduce stroke risk. Hidayati (2021) found that high heart rates can trigger heart disease (p = 0.035), which can lead to strokes [23] . Fauzi (2022) reported an average pulse rate of 92.04 beats/minute in stroke patients at the Emergency Room (IGD), with a minimum of 76 and a maximum of 128 beats/minute [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Managing blood pressure along with MAP can reduce stroke risk. Hidayati (2021) found that high heart rates can trigger heart disease (p = 0.035), which can lead to strokes [23] . Fauzi (2022) reported an average pulse rate of 92.04 beats/minute in stroke patients at the Emergency Room (IGD), with a minimum of 76 and a maximum of 128 beats/minute [24] .…”
Section: Discussionmentioning
confidence: 99%
“…4 Penderita hipertensi memiliki risiko sebelas kali lebih besar mengalami stroke dan setidaknya 51 % kematian hipertensi adalah karena stroke. 5 Pada tahun 2021, data kunjungan kasus hipertensi di Kabupaten Bantul dan Puskesmas Kasihan II menduduki posisi urutan pertama. Terdapat 102.804 kasus hipertensi di seluruh Kabupaten Bantul dan sebanyak 4.079 kasus di Puskesmas Kasihan II.…”
Section: Pendahuluanunclassified
“…One of the surveys in Indonesia that contains information about the health conditions and sociodemographic of the Indonesian people is the Indonesian Family Life Survey (IFLS). Research related to Indonesian Family Life Survey wave 5 (IFLS5) stoke data has been carried out by [10], who analysed the relationship between age, gender, blood pressure classification, diabetes, heart disease, and the incidence of stroke in patients with hypertension using the chisquare test.…”
Section: Introductionmentioning
confidence: 99%